Smart client deployment with ClickOnce : deploying Windows Forms applications with ClickOnce - Noyes, Brian (Microsoft .NET development series., 2006)
"ClickOnce demos may look simple, but those techniques only work for simple applications. Brian Noyes gives us the information we need to use ClickOnce in the real world, and he does it with a comprehensive and organized presentation. If you expect your smart client application to move very far beyond 'Hello, World, ' you'll want this book to help you deploy it."--Billy Hollis, president/owner, Elysian Consulting, Microsoft Regional Director "Once again Brian has outdone himself. As a writer, I tend to be very critical of all technical publications, including my own ... and it is such a pleasure to read anything Brian writes because he studies his topics well, resulting in an accurate, thorough, yet concise piece of work. ClickOnce being a new technology that deals with the pains we all have with application deployment, versioning, and security, it is important to have a text that will guide you through the learning process, give you sound advice for adopting the technology, and explain why you should even care. Brian gives his readers all of that." - Michele Leroux Bustamante, chief architect, IDesign, Microsoft Regional Director "ClickOnce is the key to Windows and smart client deployment. Brian's book is the key to successfully using ClickOnce. This book walks you through using ClickOnce, from the basics to advanced scenarios. It is an excellent resource." - Rockford Lhotka, principal technology evangelist, Magenic Technologies, Microsoft Regional Director "Brian covers ClickOnce with a view to real-world deployment issues, which isobviously based on real-world experience. In and of itself, that is enough forme to buy the book. However, it is an even better investment by virtue of thefact that ClickOnce is a core part of the .NET Framework for Windows Forms2.0 now, and Windows Presentation Foundation in the future." - Michael Weinhardt, SDK programmer/writer, Application Model, Windows Presentation Foundation, Microsoft "This book covers the most important ingredient needed for the success of asmart client application-deployment. The author's unassuming writing style, combined with his in-depth coverage of the topic, makes this book an invaluableresource for all serious smart client developers." - Vishwas Lele, principal architect, Applied Information Sciences, Microsoft Regional Director Microsoft's new ClickOnce auto-updating technology can radically simplify application deployment. Using it, .NET developers and architects can deliver ...